Ephemeral print culture in early modern England : sociability, politics and collecting - Somers, Tim (Studies in the eighteenth century., 2021)
Uses the collections of ephemera popular in the late seventeenth century as a way to understand the reading habits, publishing strategies and thought processes of late Stuart print culture.